Study on the Relationship between Blood Glucose Control and Diabetic Foot Ulcers at Dr. Moewardi Hospital of Surakarta - Purwanti, Okti Sri; Yetti, Krisna; Herawati, Tuti; Sudaryanto, Agus; Daryani, D (Universitas Muhammadiyah Surakarta, 2016)
Background. Diabetic foot ulcers has several negative impacts on individuals, since it disrupts one’s physical activity and psychological condition, as well as the financial loss for the treatment. The purpose of this study was to find the relationship between blood glucose control and foot ulcers. This research used observational analytic study with case-control methods. It applied purposive sampling in34 diabetes mellitus patients with foot ulcers and 34 diabetes mellitus patients without foot ulcers. Theresearch instruments were documentation study about HbA1c and incidence of diabetic ulcers. Theresults indicated there was a relationship between blood glucose control and the incidence of foot ulcers in the patients at Dr. Moewardi Hospital. The respondents with poor blood glucose control will have a chance to suffer from foot ulcers 5.800 times than those who have good blood glucose control.